Towards a Middle Way Islam in Southeast Asia: Controbutions of the Gülen Movement - Osman, Mohamed Nawab Mohamed (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
This paper intends to demonstrate how the Gulen Movement has addressed the issues facing them and remained relevant by developing a counter-trend through proactive measures to oppose extremist ideology and enhance inter-religious discussion in the Southeast Asian region. Its key thrust is to show that the Gulen Movement can reverse the current distorted state of Islam back to its original form. The teachings of Islam, which preach neither extremism nor laxness in religious matters, can accommodate cultural differences in Southeast Asia and enhance inter-religious ties between Muslims and non-Muslims in the region.DOI: 10.15408/sdi.v15i3.525